An Icelandic terrestrial record of North Atlantic cooling c. 8800–8100 cal. yr BP. (1st October 2018) - Eddudóttir, Sigrún Dögg; Erlendsson, Egill; Gísladóttir, Guðrún
Highlights: A shift in vegetation community is recorded in northwest Iceland in response to cool climate c. 8800–8100 cal. yr BP. Betula pubescens woodland development was disrupted and a more open vegetation community took hold. Colder springs/summer temperatures may have caused a significant decrease in pollen production from terrestrial plants. Terrestrial Icelandic multi-proxy records can provide insight into Holocene climate variability in the North Atlantic.